Odpowiedzi

Najlepsza Odpowiedź!
2010-04-11T18:13:06+02:00
A)(3x-5)(4x+2)+(3-x)(x+4)=12x²+6x-20x-10+3x+12-x²-4x=11x²-15x+2
b)(9x+2)(-3x+1)+(-2x-3)(x+1)=-27x²+9x-6x+3-2x²-2x-3x-3 = -29x²-2x
c)(2x-3)(2x+6)-(x-5)(x+4)=2x²+12-6x-18-x²-4x+5x+20=x²-5x+2
1 5 1
2010-04-11T18:18:13+02:00
A)(3x-5)(4x+2)+(3-x)(x+4)= (12x²+6x-20x-10)+(3x+12-x²-4x)= 12x²-14x-10+(-x+12-x²)= 12x²-14x-10-x012-x²=11x²-15x+2

b)(9x+2)(-3x+1)+(-2x-3)(x+1)=(-27x²+9x-6x+2)+(-2x²-2x-3x-3)= -27x²+3x+2-2x²-5x-3= -29x²-2x-1

c)(2x-3)(2x+6)-(x-5)(x+4)= (4x²+12x-6x-18)-(x²+4x-5x-20)=
4x²+6x-18-(x²-x-20)= 4x²+6x-18-x²+x+20=3x²+7x+2